2019
DOI: 10.1016/j.jmat.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

First-principles prediction of magnetically ordered half-metals above room temperature

Abstract: Half-metallicity (HM) offers great potential for engineering spintronic applications, yet only few magnetic materials present metallicity in just one spin channel. In addition, most HM systems become magnetically disordered at temperatures well below ambient conditions, which further hinders the development of spin-based electronic devices. Here, we use first-principles methods based on density functional theory (DFT) to investigate the electronic, magnetic, structural, mixing, and vibrational properties of 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The obtained values of band gaps are consistent with the reported values. 22 However, the bands at the Fermi level of spin up states do not shi, thereby validating the half-metallicity in these alloys.…”
Section: Electronic and Magnetic Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The obtained values of band gaps are consistent with the reported values. 22 However, the bands at the Fermi level of spin up states do not shi, thereby validating the half-metallicity in these alloys.…”
Section: Electronic and Magnetic Propertiesmentioning
confidence: 98%
“…Recently, half-Heusler compounds with 8 valence electrons, due to their compatible electronic structure and thermal stability, are regarded as prospective materials for spintronic applications. 22 Motivated by the aforementioned characteristics and multi-dimensional applications, cubic half-metallic RbTaZ (Z: Si, Ge) Heusler alloys have been selected in the present work. There are no detailed results regarding the mechanical characteristics, thermodynamic and transport properties of these alloys; therefore, our results would pose their future applications in energy harvesting and spintronic technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al carried out HTP calculations on 378 half Heuslers and identified 26 semiconductors, 45 half metals, and 34 nearly half metals, which are thermodynamically stable [80]. Another recent work investigated the alkaline element based half Heuslers and found 28 FM materials out of 90 compositions [542]. Importantly, for half Heusler materials, it is not enough to consider only the binary competing phases, but also possible ternary compounds as there are many crystal structures which can be stabilized based on the 18-electron rule for the 1:1:1 composition [543].…”
Section: Heusler Compoundsmentioning
confidence: 99%
“…FM compounds with a large change in magnetic entropy and adiabatic temperature T ad (change in temperature of the system under adiabatic condition without exchange of heat) across the transition temperature near room temperature are potential candidates for technological applications such as magnetic refrigeration. In recent times, Heusler compounds have become materials of topical interest for their multifunctional and peculiar properties such as topological insulators, , Weyl semimetals, spin-gapless semiconductors, shape memory effect, , half-metals, exchange bias, large magnetoresistance, and magnetocaloric effect. , …”
Section: Introductionmentioning
confidence: 99%